HIV-Stigma in Nigeria: Review of Research Studies, Policies, and Programmes - Clifford O. Odimegwu; Joshua O. Akinyemi; Olatunji O. Alabi (AIDS Research and Treatment)
Nigeria has about 3.8 million people living with HIV, the second largest globally. Stigma and discrimination are major barriers to testing, treatment uptake, and adherence. In this review, we synthesized information on research studies, policies, and programmes related to HIV-stigma in Nigeria. This was with a view to identify critical areas that research and programmes must address in order to accelerate the progress towards zero (new infections, discrimination, and death) target by year 2030. Existing studies were mostly devoted to stigma assessment using varieties of measures. Research, policies, and programmes in the past two decades have made very useful contributions to stigma reduction. We identified the need for a consistent, valid, and objective measure of stigma at different levels of the HIV response. Nigeria does not lack relevant policies; what needs to be strengthened are design, planning, implementation, monitoring, and evaluation of context-specific stigma reduction programmes.